Enhancing Students’ Speaking Skills in Discussion Texts Through Problem-Based Learning: A Classroom Action Research - Titi Rokhayati; Shofia Lina Nafisah; Frisca Putri Agillia; Sujay Kanthal (TAMANSISWA INTERNATIONAL JOURNAL IN EDUCATION AND SCIENCE, 2025)
This classroom action research investigates the impact of Problem-Based Learning (PBL) integrated with debate techniques in improving Grade 12 students' speaking skills in learning discussion texts in a public senior high school in Purworejo. The research is conducted in two cycles, the study follows Kemmis and McTaggart's action research phases: planning, acting, observing, and reflecting. Each cycle involved structured activities, including debates, real-world problem analysis, and collaborative discussions, to enhance students' fluency, accuracy, and critical thinking. Data were collected through pre- and post-tests, observations, and questionnaires. Results revealed a significant improvement in speaking performance, with average post-test scores increasing from 73.86 to 86.43 across the cycles. The findings highlight and point to the effectiveness of combining PBL and debates in fostering active participation, boosting confidence, and improving speaking proficiency in English as a Foreign Language (EFL) context. These outcomes underline the potential of interactive and student-centered approaches to overcome challenges in EFL speaking skills development.